Reevaluating the Profitability, Performance, and Stability of Sharia Banks in Indonesia Using the Eagles Framework - Kurnia, Rahmat; Fenitra, Rakotoarisoa Maminirina; Hasan, Nugraha; Melzatia, Haura Hazimah (Tasharruf: Journal Economics and Business of Islam, 2024)
Islamic banking in Indonesia has experienced rapid development in recent years. This encourages the importance of reviewing the financial performance of Islamic Commercial Banks (BUS) to determine the level of health and efficiency. The purpose of this study is to analyze the financial performance of BUS during the period 2018-2022 using the EAGLES method. As well as comparing financial performance between BUSs during the 2018-2022 period. This study uses quantitative methods with secondary data sourced from BUS Annual Reports for the 2018-2022 period. Financial performance is measured using the EAGLES method which includes ROA, ROE, NPF, DGR, LGR, FDR, CAR, and SRQ ratios. The results showed that there were differences in the ratios calculated on BUS during the 2018-2022 period. Overall, BUS shows a fairly healthy financial performance with some BUSs that have better performance than others. The conclusion of this study is that the financial performance of BUSs during the 2018-2022 period shows a positive trend with some BUSs that have better performance than others. The use of the EAGLES method provides a comprehensive overview of BUS financial performance and can be used to compare performance between BUSs.